Mapping of Abutilon Mosaic Geminivirus Minichromosomes - Pilartz, Marcel (American Society for Microbiology, 2003)
The single-stranded circular DNA of Abutilon mosaic geminivirions is complemented to double-stranded DNA by host proteins after infecting cells. This double-stranded DNA serves as a template for replication as well as transcription and is assembled into host nucleosomes, yielding circular viral minichromosomes. Their chromatin structure was analyzed by use of isolated nuclei combining nuclease sensitivity assays with ligation-mediated PCR, evaluating nucleosomal ladders and topoisomer distributions in one- and two-dimensional gels by blot hybridization. Viral minichromosomes were found to exist in at least two defined structures covered with 11 or 12 nucleosomes, leaving open gaps accessible for interactions with other host factors. Nucleosome-free gaps were colocalized with promoter structures and the origin of replication in both components of genomic DNA (DNA A and DNA B). Nucleosomes were positioned over the entire viral DNA in at least two alternative phases with different periodicities. The distribution of topoisomers of monomeric viral circular double-stranded DNA confirmed the presence of variable chromatin structures revealing maximum frequencies of molecules with either 11, 12, or 13 superhelical turns (corresponding to respective numbers of nucleosomes) at maximal frequency at different stages during leaf development of infected plants. The role of variable chromatin structures for gene regulation of geminiviruses is discussed.